Synthesis and biological evaluation of phospholane and dihydrophosphole analogues of the glutamate receptor agonist AP4 - Conway, S; Miller, J; Bond, A; Clark, B; Jane, D (2002)
The syntheses and preliminary pharmacological characterisation of two novel cyclic phosphinic acid-containing amino acids designed as conformationally restricted analogues of the metabotropic glutamate receptor agonist AP4 (1) are reported.